A thin film optoelectronic photodetector of spherical and linear resonators via one-pot synthesis of Bi(III) oxide/polypyrrole nanocomposite - Fatemah H. Alkallas; Mohamed Rabia; Fedor V. Kusmartsev; Amira Ben Gouider Trabelsi (Scientific Reports)
Abstract We report the fabrication and characterization of a Bi(III) oxide/polypyrrole (Bi2O3/Ppy) nanocomposite thin film optoelectronic photodetector synthesized by a simple one-pot method. The nanocomposite consists of spherical Bi2O3 nanoparticles embedded in a Ppy matrix, forming a porous structure with a high surface area. The XRD analysis reveals that the Bi2O3 nanoparticles have a poly-crystalline nature with a crystal size of 40 nm and an optical bandgap of 2.86 eV. The SEM images show that the nanoparticles are agglomerated into clusters of about 100 nm in diameter, with pores of about 200 nm in width. The device exhibits a high sensitivity to light, as evidenced by the increase of the photocurrent density (Jph) from − 0.06 mA.cm−2 in the dark to -0.12 mA.cm−2 under illumination at -2.0 V. The device also shows a wavelength-dependent response, with the highest responsivity (R) of 1.0 and 0.9 mA/W and detectivity (D) of 0.221 × 109 and 0.20 × 109 Jones at photon energies of 3.6 eV and 2.8 eV, respectively. The Bi2O3/Ppy nanocomposite is a promising material for low-cost, high-performance optoelectronic applications, making it a superior choice over many contemporary devices reported in recent literature.